The free trade agreement betwen Colombia and USA :what can happen to Colombia? (2009)
In order to assess the impact of a Free Trade Agreement (FTA) between Colombia and the United States of America, we describe the characteristics of the Colombian economy emphasizing its trade patterns and perspectives and identifying the sectors and regions that are likely to be the most sensitive to a FTA. We argue that the effects of a bilateral trade agreement between the USA and Colombia would be similar to those of past trade reforms. We first analyze the effect of past reforms over a diverse sample of countries such as Chile, Colombia and Mexico and then, using an applied general equilibrium model, simulate the effects over the Colombian economy of a bilateral agreement with USA. The simulations show that, although small, there is an increase in welfare and production of the Colombian consumers and firms.